Pengaruh Jahe Hangat Dalam Mengurangi Mual, Muntah Ibu Hamil Dengan Hipermesis Gravidarum - Lazdia, Wenny; Putri, Nadia Eka (Universitas Fort De Kock Bukittinggi, 2020)
Background: Pregnancy is the condition of a woman who has an embryo in her womb that continues to develop over time. Normal pregnancy occurs for 40 weeks between the last menstrual period and birth (38 weeks) from conception. Based on the phenomenon obtained in the Muara Labuh Health Center work area in July 2018, it was found that 47 women were pregnant with hyperemesis gravidarum. This study aims to determine the effect of giving ginger. Method: Research methods Quasy Experiment control design post-post test With the Pretest and Postest approach to see the effect of giving warm ginger water to the reduction of nausea and vomiting in pregnant women with hyperemesis gravidarum trimester 1. Results: The results of warm ginger administration research Interventions have a significant effect on decreasing hyperemesis gravidarum in the first trimester of pregnancy women with a decrease in the average difference between the intervention group and the control group was 10.87 RINVR score (Rhodesh INdekx from Nusea, Vomiting, and Retching) and p-value = 0,000, where the decrease in the intervention group was greater than control group. Conclusion: It is expected that respondents namely trimester I pregnant women can use warm ginger steeping in overcoming or reducing the frequency of hyperemesis gravidarum because based on the results of research on boiling water ginger is effective in reducing the severity of hyperemesis gravidarum in pregnant women